2017
DOI: 10.1177/1091581817735227
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Toxicity Assay for Food Additive Tartrazine Using Zebrafish (Danio rerio) Embryo Cultures

Abstract: Tartrazine (TTZ) is an azo dye used as a colorant in food products, drugs, and cosmetics. The present study evaluates the impacts of TTZ on embryonic development of zebrafish ( Danio rerio). Laboratory-raised D. rerio embryos (n = 20/concentration) were exposed to graded dilutions of TTZ (0, 0.1, 1, 2, 3, 4, 5, 10, 20, 30, 40, 50, 75, and 100 mM) from gastrulation stage (5.25 hours postfertilization [hpf]) until hatching and developmental trajectory was traced up to day 7. The no observed effect concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…A consistent decrease in heart rate was accomplished in all those larvae that exhibited pericardial edema, indirectly clues the impairment in the cardiac function. In our earlier studies, also we observed that pericardial edema was accompanied by decreased heart rates in chemical (Coumarin derivatives) pharmaceuticals (Cox inhibitors/acetaminophen) and FA (tartrazine) exposed zebrafish embryos and resultant larvae (Anegundi & Pancharatna, , ; David & Pancharatna, , ; Joshi & Pancharatna, ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…A consistent decrease in heart rate was accomplished in all those larvae that exhibited pericardial edema, indirectly clues the impairment in the cardiac function. In our earlier studies, also we observed that pericardial edema was accompanied by decreased heart rates in chemical (Coumarin derivatives) pharmaceuticals (Cox inhibitors/acetaminophen) and FA (tartrazine) exposed zebrafish embryos and resultant larvae (Anegundi & Pancharatna, , ; David & Pancharatna, , ; Joshi & Pancharatna, ).…”
Section: Discussionmentioning
confidence: 82%
“…MKBW2546V), AO and Tricaine were purchased from Sigma-Aldrich (St. Louis, MO, USA), and other chemicals were procured from Hi-media (Mumbai, India). The embryo (E3) medium (5 mM NaCl; 0.17 mM KCl; 0.33 mM CaCl 2 ; 0.33 mM MgSO 4 ) was prepared as per the protocol described earlier (David & Pancharatna, 2009a, 2009bJoshi & Pancharatna, 2017;Westerfield, 2007). As E110 is a completely water-soluble compound (Rovina et al, 2016) all the dilutions (0.1, 1, 2, 3, 4, 5, 10, 20, 30, 40, 50 and 100 mM) of exposure media were prepared freshly in E3 medium just before their use.…”
Section: Calculation Of Median Lethal Concentrationmentioning
confidence: 99%
“…(20) reported that TAZ exhibits no maternal or developmental toxicity in Osborne-Mendel rats when administered by gavage at doses of 0, 60, 100, 200, 400, 600, or 1,000 mg/kg body weight/day on gestational days 0–19. A recent study reported that TAZ up to 10 mM is not embryotoxic nor teratogenic to zebrafish embryos (21). However, no previous study has examined the teratogenic potential of TAZ when administered at several folds its acceptable daily intake (ADI).…”
Section: Introductionmentioning
confidence: 99%
“…33 The decreased hatching rate has been observed in zebrafish embryos exposed to pharmaceuticals (including acetaminophen and auranofin), nanomaterials and nanoparticles, organic pesticides, and metal ions. 19,35,36 The heart is one of the first organs observed during zebrafish development. Heart rate is an important target for developmental toxicity in zebrafish, as an indicator of cardiac function.…”
Section: Discussionmentioning
confidence: 99%
“…The test concentrations were selected following the OECD Test Guidelines (2013) and methods of Joshi and Katti. 19 All experiments were done in triplicate, and each assay was repeated 3 times.…”
Section: Experimental Designmentioning
confidence: 99%